Beyond nature : animal liberation, Marxism, and critical theory - Maurizi, Marco, 1974- (Historical materialism book series, 2021)
"In Beyond Nature Maurizi tackles the animal question from an unprecedented perspective: strongly criticizing the abstract moralism that has always characterized animal rights activism, the author proposes a historical-materialistic analysis of the relationship between humans and non-humans. By contrasting the thinking of Hegel, Marx and the Frankfurt School with classical authors in the field of animal rights (such as Singer, Regan, and Francione) this text offers an alternative, social and dialectical theory of animality and a different practical approach to the problem of animal suffering. The hopes for change placed in veganism, liberationism and animal activism are here assumed in a political, revolutionary perspective, in which human and animal liberation finally cease to oppose each other"--